Bedaquiline: Current status and future perspectives. (June 2021) - Khoshnood, Saeed; Goudarzi, Mehdi; Taki, Elahe; Darbandi, Atieh; Kouhsari, Ebrahim; Heidary, Mohsen; Motahar, Moloudsadat; Moradi, Melika; Bazyar, Hadi
Highlights: The development of antibiotic-resistant tuberculosis is a main threat worldwide. Based on WHO reports, it is estimated that more than 500 000 new cases of antibiotic-resistant TB occur annually. Bedaquiline, a novel anti-TB drug, has significant minimum inhibitory concentrations (MICs) both against drug-susceptible and drug-resistant TB. This review summarises the available data on Bedaquiline resistance, antimicrobial properties, and provides new perspectives. Abstract: The development of drug-resistant tuberculosis (TB) is a major threat worldwide. Based on World Health Organization (WHO) reports, it is estimated that more than 500 000 new cases of drug-resistant TB occur annually. In addition, there are alarming reports of increasing multidrug-resistant TB (MDR-TB) and the emergence of extensively drug-resistant TB (XDR-TB) from different countries of the world. Therefore, new options for TB therapy are required. Bedaquiline (BDQ), a novel anti-TB drug, has significant minimum inhibitory concentrations (MICs) both against drug-susceptible and drug-resistant TB. Moreover, BDQ was recently approved for therapy of MDR-TB. The current narrative review summarises the available data on BDQ resistance, describes its antimicrobial properties, and provides new perspectives on clinical use of this novel anti-TB agent.